Peranan Sekuen Diffusion Weighted Imaging (DWI) Pada Pemeriksaan MRI Soft Tissue Leher Kasus Kanker Nasofaring (Studi Literatur) - Zefanya G. Pandelaki; Annila Suryo Saputro; Ni Putu Rita Jeniyanthi (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to determine the role of the Diffusion Weighted Imaging (DWI) sequence in Soft Tissue MRI examinations of the neck in cases of nasopharyngeal cancer and to determine the advantages of using the Diffusion Weighted Imaging (DWI) sequence in MRI Soft Tissue examinations of the neck in cases of nasopharyngeal cancer. The research method used was a descriptive qualitative research method with a literature study method. The results of the literature review research showed: 1) Nasopharyngeal cancer, especially squamous cell carcinoma, can be treated with radiation therapy where treatment failure is still a serious problem, especially in advanced cases. DWI and ADC are imaging methods that utilize the movement of water inside. DWI provides additional information regarding response to treatment in hard-to-reach cases of nasopharyngeal cancer. plays an important role in detection, evaluation of response to treatment, and early monitoring of chemoradiotherapy therapy. DWI also provides information that helps distinguish between tissue experiencing post-RTH fibrosis and areas that may contain active cancer cells. DWI and ADC are also useful in tumor staging, delineation of target volumes, and detection of tumor recurrence. Elevated ADC may be indicative of a favorable response to therapy, whereas low pretreatment ADC values ​​may predict a favorable response. In the diagnosis of nasopharyngeal cancer, DWI and ADC also help differentiate squamous cell carcinoma subtypes, predict response to chemoradiation therapy, and determine the appropriate time for alternative treatment regimens. 2) DWI and ADC provide advantages in the diagnosis and monitoring of nasopharyngeal cancer. DWI can image restrictions on water diffusion within tissue, helping to detect areas of high cell density associated with tumors. Its advantages include sensitivity to microenvironmental changes and the ability to early identify recurrence or secondary cancer post-radiation therapy.